Enhancing Polyphenol Delivery and Efficacy Using Functionalized Gold Nanoparticles: Antioxidant and Antibacterial Properties - Siham Bouaouz; Miriam Chavez; Cornelia E. Peña González; Daniel Rojas; Alberto Escarpa; Paula Ortega; F. Javier de la Mata (Bioinorganic Chemistry and Applications)
Research into the use of nanoparticles to enhance the delivery and efficacy of polyphenols is a topic of growing interest in the fields of nanotechnology, pharmacology and food science. Nanoparticles, due to their small size and high surface area, can improve the stability, solubility and bioavailability of polyphenols. Combining polyphenols with other bioactive compounds within nanoparticles can create synergistic effects, enhancing their overall therapeutic potential. In this work, we present a new polyethylene glycol (PEG) capping ligand modified with caffeic acid (CA), HS-PEG-CA and two types of gold nanoparticles: (i) coated with a PEG-thiol derivative functionalized with CA (HS-PEG-CA) (homofuncionalized NP) and (ii) HS-PEG-CA cationic carbosilane dendrons with antibacterial properties (heterofuncionalized NP). The antioxidant capacity of the CA, in three systems, has been studied by different techniques such as FRAP, DDPH and cyclic voltammetry, demonstrating that it is preserved when it is supported on the NP and increases when it is part of the PEG ligand. In addition, heterofuntionalized NP showed activity against S. aureus and HS-PEG2K-CA ligand can effectively anchor to gold substrates.